TREN RETURN ON ASSET (ROA) PADA PT ASTRA AGRO LESTARI TBK PERIODE 2012 – 2016 - Marsel B. Robot; Rine ., Kaunang; Lorraine W. Th. Sondak (AGRI-SOSIOEKONOMI, 2017)
The study aims to determine the trend of return on assets (ROA) at PT. Astra Agro Lestari Tbk from 2012 to 2016. The data used are secondary data, obtained in the form of data that has been collected, processed and published by other parties namely the Indonesia Stock Exchange in the form of data obtained from the corner of the Indonesia Stock Exchange in the Faculty of Economics and Business University Sam Ratulangi Manado. Data analysis used is descriptive data analysis method that is by describing an object so that can be drawn conclusion. This descriptive data analysis aims to determine the trend of return on assets (ROA) at PT Astra Agro Lestari TBK in 2012-2016 which will be presented in the form of tables and graphs. The results showed that Trends Return On Assets (ROA) at PT. Astra Agro Lestari, Tbk in 2013 there is a decrease in ROA from 2012, then in 2014 there is an increase compared to the year 2013. In 2015 there is a decrease in ROA from 2014, and in 2016 ROA increase in comparison to 2015. This decline occurred because the average CPO price drops. The fall in CPO prices leads to a decrease in gross revenues followed by a decrease in profits and will further lead to a decrease in ROA.